2002
DOI: 10.1073/pnas.132598099
|View full text |Cite
|
Sign up to set email alerts
|

DT40 cells lacking the Ca 2+ -binding protein annexin 5 are resistant to Ca 2+ -dependent apoptosis

Abstract: Annexins are widely expressed Ca 2؉ -dependent phospholipidbinding proteins with poorly understood physiological roles. Proposed functions include Ca 2؉ channel activity and vesicle trafficking, but neither have been proven in vivo. Here we used targeted gene disruption to generate B-lymphocytes lacking annexin 5 (Anx5) expression and show that this results in reduced susceptibility to a range of apoptotic stimuli. By comparison B-lymphocytes lacking annexin 2 (Anx2) showed no such resistance, providing eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 44 publications
2
29
0
2
Order By: Relevance
“…These activities are thought to be due to its ability to bind phospholipids, although it is not clear whether these activities are relevant to physiological function. However, as we showed in the gonadotropes, annexin A5 may be at least necessary for an intracellular signaling in some cell types [14][15][16]. …”
mentioning
confidence: 63%
See 1 more Smart Citation
“…These activities are thought to be due to its ability to bind phospholipids, although it is not clear whether these activities are relevant to physiological function. However, as we showed in the gonadotropes, annexin A5 may be at least necessary for an intracellular signaling in some cell types [14][15][16]. …”
mentioning
confidence: 63%
“…showed that annexin A5 knock-out lymphocytes become resistant to various apoptotic stimuli [16]. Although these findings do not form a single clear picture, most reports indicate that annexin A5 participates in protein-protein signaling complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Although Ca 2+ ions seem to signal between the ER and mitochondria, whether or how this promotes caspase activation is obscure (see below). One potential mediator of Ca 2+ signaling is the Ca 2+ -binding annexin-5, recently shown to be required for apoptosis in response to certain insults (Hawkins et al 2002). Because cells lacking annexin-5 failed to release cytochrome c from mitochondria, and chelators of Ca 2+ ions protected wild-type cells, annexin-5 might transduce a critical Ca 2+ signal from the ER needed for mitochondrial disruption.…”
Section: Potential Role Of the Er In Apoptosismentioning
confidence: 99%
“…Other annexin-knockout models (mice lacking annexins A1, A2, A5 or A6, and DT40 chicken pre-B cells lacking annexin A5) also show no obvious phenotype related to a primary defect in vesicle docking and/or fusion events (Brachvogel et al, 2003;Hannon et al, 2003;Hawkins et al, 1999;Hawkins et al, 2002;Ling et al, 2004;Song et al, 2002). This indicates that the annexins targeted in these mice do not serve as essential factors in vesicle docking and/or fusion or that such functions are redundant or taken over by another member of the family during mouse development.…”
Section: Membrane/protein Transport Steps Involving Annexinsmentioning
confidence: 99%